2017
DOI: 10.3389/fpls.2017.01129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wild Lentil Species as Genetic Resources to Improve Drought Tolerance in Cultivated Lentil

Abstract: Increasingly unpredictable annual rainfall amounts and distribution patterns have far reaching implications for pulse crop biology. Seedling and whole plant survival will be affected given that water is a key factor in plant photosynthesis and also influences the evolving disease spectrum that affects crops. The wild relatives of cultivated lentil are native to drought prone areas, making them good candidates for the evaluation of drought tolerance traits. We evaluated root and shoot traits of genotypes of cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…Experimental data was analyzing using. The program Statgraphics Centurion v. 16. Before the analysis of variance, the validity of normality assumption was checked by the Shapiro-Wilk test and the homogeneity of variance using the Levene test.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data was analyzing using. The program Statgraphics Centurion v. 16. Before the analysis of variance, the validity of normality assumption was checked by the Shapiro-Wilk test and the homogeneity of variance using the Levene test.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This has resulted in substantial scientific efforts being invested in the elucidation of abiotic stress tolerance mechanisms in plants, to help mitigate those adverse effects on crop yields [10][11][12][13]. Data generated from these studies have contributed to define appropriate strategies for breeding of enhanced crop stress tolerance [14][15][16]. Paradoxically, most studies on abiotic stress tolerance mechanisms have been conducted in model plants, such as Arabidopsis thaliana, or in some major crops, which are relatively sensitive to stress [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Lentil belongs to genus Lens which is extremely versatile, oldest cultivated legume and is exceedingly healthy having high fibre and high protein content [1]. Due to increase in its consumption around the world, lentil production has boosted from 4.7 million tonnes to 7.6 million tonnes from 2010 to 2017 (FAOSTAT) primarily in regions of northern plains of North America and Australia [2]. Lentil production can be enhanced further if we can put a check on a major agricultural obstacle of acidic soils i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on wild lentil germplasm in the field and indoors, showed the phylogenetic relationship between genotypes in the context of drought tolerance but root traits were not characterized ( Singh et al, 2016 ). A baseline study of drought tolerance of wild lentil species showed that variation in drought avoidance exists between and within species ( Gorim and Vandenberg, 2017 ). No comprehensive study exists for wild lentil root traits and root distribution patterns in different soil layers.…”
Section: Introductionmentioning
confidence: 99%